ANALISIS VECTOR AUTOREGRESSION (VAR) TERHADAP STABILITAS TOTAL ASET PERBANKAN SYARIAH DI INDONESIA PERIODE 2003-2012 - Sudrajat, Anton (Islamic Economics Journal, 2013)
High public expectation towards Islamic banking can help support the growth in assets and third-party funds and assist the distribution of Islamic banking financing. The purpose of this study is to analyze the stability of the total assets of the Islamic banking on period November 2003 to October 2012. The method of study is the Vector Autoregression (VAR). The results show that the variables Deposits and FDR have significant positive effect on total assets of Islamic banking in the long run, while the NPF variable statistically affect Islamic banking assets in the short term. Thus, the increase in total assets of Islamic banking is influenced by the size of the public trust towards NPF of Islamic banking with an average of 4.03%, far below the stipulated NPL/NPF from Bank Indonesia, which is 5% during the period November 2003 to October 2010.